Prostaglandin E2 and F2alpha Modulate Urinary Bladder Urothelium, Lamina Propria and Detrusor Contractility via the FP Receptor - Stromberga, Zane; Chess-Williams, Russ; Moro, Christian (Frontiers in Physiology, 2020)
Current pharmacological treatment options for many bladder contractile dysfunctions are not suitable for all patients, thereby bringing interest to the investigation of therapies that target a combination of receptors. This study aimed to compare responses of PGE2 on the urinary bladder urothelium with lamina propria (U&LP, also called the bladder mucosa) or detrusor smooth muscle and attempt to identify the receptor subtypes mediating PGE2 contractile responses in these tissues. In the presence of selective EP1 – 4 receptor antagonists, varying concentrations of PGE2 were applied to isolated strips of porcine U&LP and detrusor that were mounted in organ baths filled with Krebs-bicarbonate solution and gassed with carbogen. The addition of PGE2 (1 µM and 10 µM) and PGF2α (10 µM) to U&LP preparations caused significant increases in the baseline tension and in the spontaneous phasic contractile frequency. In detrusor preparations, significant increases in the baseline tension were observed in response to PGE2 (1 µM and 10 µM) and PGF2α (10 µM), and spontaneous phasic contractions were initiated in 83% of preparations. None of the selective PGE2 receptor antagonists inhibited the increases in baseline tension in both U&LP and detrusor. However, the antagonism of PGF2α receptor showed significantly inhibited contractile responses in both layers of the bladder. This study presents prostaglandin receptor systems as a potential regulator of urinary bladder contractility. The main contractile effects of PGE2 in both U&LP and detrusor are mediated via the FP receptor with no observed contribution from any of the four EP receptors.